2014
DOI: 10.1007/s10886-014-0496-z
|View full text |Cite
|
Sign up to set email alerts
|

Defense in the Aeolidoidean Genus Phyllodesmium (Gastropoda)

Abstract: The genus Phyllodesmium (Aeolidoidea, Gastropoda) comprises shell-less marine snails, whose defense strategies are not well investigated yet. Here we report results of the first chemical investigation of P. briareum, as well as a re-investigation of P. longicirrum and P. magnum. Briarane diterpenes were isolated from P. briareum, and their origin could be traced to its prey organism Briareum sp. (Octocorallia). Considerable enrichment of the soft coral secondary metabolites in the slug was shown. Re-investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 54 publications
0
22
0
Order By: Relevance
“…; Bogdanov et al. ). Thus, although nematocyst sequestration may be an important defense mechanism across most of Aeolidida, it is not present in all species in this group and appears to have been lost at least once.…”
Section: Nematocyst Sequestration In Four Metazoan Lineagesmentioning
confidence: 98%
“…; Bogdanov et al. ). Thus, although nematocyst sequestration may be an important defense mechanism across most of Aeolidida, it is not present in all species in this group and appears to have been lost at least once.…”
Section: Nematocyst Sequestration In Four Metazoan Lineagesmentioning
confidence: 98%
“…To reach this, chemical defense medated by natural products plays a major role. It was already shown that the slugs incorporate and enrich bioactive metabolites from their food source (Bogdanov et al, 2014, 2016). However, it has to be kept in mind that compounds present in the food source may be rather produced by associated microorganisms, e.g., bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…The extraction procedure was analogous as described in [11]. The ethanolic storage solution was combined with the MeOH extract (3 × 150 mL) of the slug biomass and the solvents were evaporated.…”
Section: Methodsmentioning
confidence: 99%